PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CAMTASIA STUDIO BERBASIS POWERPOINT - Yusuf, Daud (Sainstek, 2012)
Camtasia studio application is an application that can be used to create learning media. With this application the bias produces video based learning powerpoint and desktop. To make this application first then do is to install the application on your laptop / computer. Once installed the application will appear in the powerpoint application. When has emerged then we can directly start making video. After we finished recording directly save files recorded in accordance with the format we want. Camtasia Studio.